AL-SHĀFI’Ī’S PERSPECTIVE ABOUT THE ECLIPSE PRAYER AT FORBIDDEN TIMES FOR PRAYING - Inayah, Maulida (Fakultas Syari'ah dan Hukum UIN Walisongo, 2023)
The eclipse prayer, considered Sunnah Muakkad, presents different points of view among the ulama. Most jurists believe these prayers are prohibited during haram times (taḥrīm) because the ḥadīth applies to all prayers. It is different from al-Shāfi'ī who allows eclipse prayers at any time, even during taḥrīm. Since most Indonesian people adhere to the al-Shāfi'ī school of thought, understanding the basis of its ijtihād is essential. With a qualitative method, this literature article uses a descriptive-analytical method, with the primary source being the book al-Umm. This article produces two main findings. First, al-Shāfi'ī justifies the eclipse prayer during taḥrīm because of the general nature of the ḥadīth restrictions and the particular reason for the eclipse prayer. Second, the legal reasoning uses qiyās, aligning missed prayers with valid reasons at taḥrīm times.